Advances in experimental social psychology - Zanna, Mark P.; ScienceDirect eBooks (San Diego : Academic Press, 1995)
Advances in Experimental Social Psychology continues to be one of the most sought after and oft cited series in this field. Containing contributions of major empirical and theoretical interest, this series represents the best and the brightest in new research, theory, and practice in social psychology.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Social psychology; Social psychology -- Research; Social psychology; Social psychology -- Research; Electronic books